Chemical composition and source analysis of carbonaceous aerosol particles at a mountaintop site in central Sweden. Issue 1 (1st January 2017) - Franke, Vera; Zieger, Paul; Wideqvist, Ulla; Acosta Navarro, Juan Camilo; Leck, Caroline; Tunved, Peter; Rosati, Bernadette; Gysel, Martin; Salter, Matthew Edward; Ström, Johan
Abstract: The chemical composition of atmospheric particulate matter at Mt. Åreskutan, a mountaintop site in central Sweden, was analysed with a focus on its carbonaceous content. Filter samples taken during the Cloud and Aerosol Experiment at Åre (CAEsAR 2014) were analysed by means of a thermo-optical method and ion chromatography. Additionally, the particle light absorption and particle number size distribution measurements for the entire campaign were added to the analysis. Mean airborne concentrations of organic and elemental carbon during CAEsAR 2014 were OC = 0.85 0.80 g m and EC = 0.06 0.06 g m, respectively. Elemental to organic carbon ratios varied between EC/OC = 0.02 and 0.19. During the study a large wildfire occurred in Västmanland, Sweden, with the plume reaching our study site. This led to significant increases in OC and EC concentrations (OC = 3.04 0.03 g m and EC = 0.24 0.00 g m ). The mean mass-specific absorption coefficient observed during the campaign was = 9.1 7.3 m g (at wavelength = 637 nm). In comparison to similarly remote European sites, Mt. Åreskutan experienced significantly lower carbonaceous aerosol loadings with a clear dominance of organic carbon. A mass closure study revealed a missing chemical mass fraction that likely originated from mineral dust. Potential regional source contributions of the carbonaceous aerosol were investigated using modelled air mass back trajectories. This source apportionment pointed to a correlation between high EC concentrations and air originating from continental Europe. Particles rich in organic carbon most often arrived from highly vegetated continental areas. However, marine regions were also a source of these aerosol particles. The source contributions derived during this study were compared to emission inventories of an Earth system model. This comparison highlighted a lack of OC and EC point-sources in the model's emission inventory which could potentially lead to an underestimation of the carbonaceous aerosol reaching Mt. Åreskutan in the simulation of this Earth system model.